A Preliminary Criteria and Classification of Land Degradation Level on Dryland (Case Study : Dryland in Bogor Regency) - SANTUN R.P. SITORUS; B. SUSANTO; O. HARIDJAJA (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2011)
Optimization of dry land utilization in Indonesia including in Bogor Regency is generally still has a lot of constraints. One of the causes is land degradation. At the moment, land degradation inventory is still resulting tentative acreages, since the criterion and overcome priority were different among institutions. This research aims (1) to know variables affecting level of land degradation, and (2) to compose criterion (classes range) andclassification of land degradation level in dry land both for reconnaissance and semi-detail scales based on variables affecting level of degradation. The research was conducted at three subdistricts, namely Sukamakmur, Babakan Madang and Cigudeg subdistricts. Data was collected on surveys through a case study. Biophysical data and soil samples were collected at60 key regions (derived from 3 subdistricts x 5 land critical levels x 4 replications). On each key region, undisturbed and composite soil samples were collected, altogether 60 undisturbed and 60 composite soil samples. The data were analyzed using discriminant analysis and cluster analysis. This research was resulting three criterions (range of classes) for five variables determining level of land degradation for reconnaissance and eight variables for semi-detail scales. The five variables for reconnaissance scale were type of bedrock, slope, conservation practices (P-value), silt percentage, and land use/vegetation (Cvalue). The eight variables for semi-detail scale were type of bedrock, slope, conservation practices (P-value), silt percentage, land use/vegetation (C-value), P-available, exchangeable Al, and H. This research had also generated three degradation levels for reconnaissance and semi-detail scales. The classification of land degradation for reconnaissance scale were (1) slightly degraded land (score <16), (2) moderately degraded land (score 16-39),and (3) strongly degraded land (score >39). Whilst, the classification of land degradation for semi-detail scale were (1) slightly degraded land (score <15), (2) moderately degraded land (score 15-38), and (3) strongly degraded land (score > 38).